Desempenho em redes WLAN MU-MIMO com seleção de usuário e diversidade - Grybosi, Jorge Felipe (2019)
Multi-User (MU) MIMO schemes introduced to IEEE 802.11ac/ax amendments can achieve high throughput by means of beamforming techniques, which enables transmission of different data streams to multiple users simultaneously. However, it requires the user Channel State Information (CSI), which is not trivial to obtain in practice. Alternatively, the access point can balance the expected rate with the CSI processing overhead by choosing an appropriate number of transmitting and receiving antennas, as well as the number of users according to client channel and backlog. We propose the application of a user selection algorithm based on MU-MIMO theoretical properties and user omnidirectional SNR named PUMA (Pre-sounding User and Mode selection Algorithm), and its application on a diversity scenario. The data rate of the proposed scheme with traditional fixed-mode and exaustive search user selection and the equivalent effects on energy efficiency are compared. Results show that the PUMA advantages are enhanced in a diversity scenario when client grouping causes dramatic changes in the sum rate. In addition, by using different diversity schemes on the same WLAN configuration, different rates and consumption are obtained. Despite MRC consuming more energy during frame reception, it is the most energy-efficient receive diversity scheme, mainly because of SNR improvement.